Potentiality of heteropolytungstates as catalysts in the selective oxidation of diphenylsulfide to diphenylsulfoxide - Egusquiza, María Gabriela (2009)
The activity of complex heteropolytungstates of general formula B-α-[MII4(H2O)2(PW9O34)2]10- with M= Co(II), Zn(II), Mn(II) and Cu(II) (PWM) was investigated in the selective oxidation reaction of diphenylsulfide to diphenylsulfoxide in presence of tert-butylhydroperoxide as oxidant. The characterization of phases was performed by X Ray Powder Diffraction, XRD. All phases resulted isomorphous although PWCu is obtained as a mixture of two structural isomers [Cu2(H2O)2PW10O38]7-. The oxidation reaction was carried out in batch at 80°C using toluene as solvent and tbutylhydroperoxide 5-6 M in decane as oxidant for 6 h. The catalytic evaluation made by gas chromatography revealed a similar behavior with conversions of diphenylsulfide around 60% and high selectivity to diphenylsulfoxide near to 95% for most of phases studied while PWCu resulted the most active catalyst presenting a conversion of 84%. The activity rise was correlated with the increase of the oxidant character of the cluster metal(II).